Malnutrition: Undernutrition or overnutrition? - Hidayat Arifin; Siti Fadlilah; Sirikanok Klankhajhon (Faculty of Nursing Universitas Padjadjaran, 2022)
The definitions and terminology related to malnutrition need to be clarified. The Academy of Nutrition and Dietetics (Academy) and the American Society of Parenteral and Enteral Nutrition (ASPEN) have classified clinical nutrition into malnutrition (undernutrition), sarcopenia, frailty, and overnutrition (overweight and obese). In addition, determining indicators for determining diagnoses related to malnutrition also needs to be clarified. Thus, this information can be used by nurses and other health workers to be able to provide appropriate planning and interventions for patients with malnutrition.